Estimação da inadimplência de carteiras de crédito de micro, pequenas e médias empresas para aplicação em testes de estresse - De Luca, Adriana Regina (2020)
The objective of this work is to propose a methodology to estimate the credit’s portfolio default rate from macroeconomic variables, using a multiple linear regression model. Thereby it is possible to assess the impact of changes in the values of these variables on the credit risk of a portfolio and, thus, establish the bases for carrying out stress tests. Stress tests are risk management instruments that must be performed by financial institutions and central banks to meet regulatory requirements, but they also serve as a valuable source of information to ensure the soundness and stability of the financial system. The focus of this work is the risk associated with the credit portfolio applied to Retail Loans to establish a comparison between this segment and that of large companies.